الحواريّة في مسرح عز الدين جلاوجي السّردي - جدع, غنية (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2022)
الملخص: تبحثُ هذه الدّراسة الموسومة 'بالحواريّة في مسرح عز الدين جلاوجي' عن تشكّلات الحواريّة في نصّ مسرحي جزائري، يقوم على التّجريب سمّاه مؤسّسه بالمسرديّة، وهي تجربة تدمج أليات الكتابة المسرحيّة مع تقنيّات السرد وذلك من خلال التّركيز على حوار اللّغات عبر التّهجين، والأسلبة، والتّنويع، وكذا الحوار الخالص، وتتتبّع حوار النّصوص من خلال تناصها مع الجماليّات التّراثيّة، العربيّة، والعالميّة، دون أن تغفل خصوصيّة هذه النّصوص التّجريبيّة، وتبيّن سرّ هذا الاستحضار. كما تقف عند التخلّل الأجناسي الذي يعدّ تيمة جوهريّة في المسرديّات؛ لتكشف عن تنوّعها الأسلوبي والإيديولوجي، وذلك عبر تتبّع المنهج التّكاملي الّذي يهدف للإحاطة بهذا الموضوع من جوانب منهجيّة، ونقديّة متنوّعة. Résumé : فرنسية أو انجلزية This study tagged with ‘Dialogism in Ezz Eddin Jalaouji’s narrative Theatre’ looking for dialogisme formations in an Algerian theater text, based on exprimentation, which called by its founder «El- Massradia »,which is an experience that combines mechanics of playwriting with the technique of narration, by focusing on the dialogue of languages through hybridization, stylization, and diversification, as well as dialogue trace text dialogue, through its intertextuality with the aesthetics of arabs, and International heritage aesthetics, without ignoring the specificity of these empirical texts, and showing the secret of this evocation, as it stands at the species interference, which is an essential theme in-El- massradiat- to reveal its stylisic and ideological diversity, by following the integrative approach that aims to encompass this topic from methodological aspects miscellanneous critisism.
اطروحة دكتوراه تخصص دراسات نقدية في الأدب و اللغات
Keywords: الحواريّة- المسرديّة- حوار اللّغات- حوار النّصوص: Dilogism- Narrative- Languages dialogue- Text dialogue